Tackling Local Conflicts Caused by Renewable Energy Sources - Lessons Learned from Real-World Case Studies - Gonzalo Gamboa; Giuseppe Munda; Daniela Russi (European Regional Science Association (ERSA), 2005)
Since Kyoto Protocol, the international community is compromising itself to reduce greenhouse gases emissions. However, the implementation of energy policies, such as the construction of renewable energy installations, in many cases doesn't suit with local perceived necessities and causes conflicts. In this paper, some types of local conflicts originating by the introduction of RES are presented. The relevance of social multi-criteria evaluation (SMCE) in dealing with this type of conflicts is discussed by means of theoretical and empirical arguments. SMCE supplies a structured process to gather, synthesize and evaluate information from several sources, which can be used as input for social debate and decision-making. In SMCE, the use of social research provides insights on the different and legitimate values and interests involved. Also, multi/inter disciplinarity gives information about the alternatives' impacts on different dimensions (environmental, social, economic, and so on). These data aren't translated in a common unit of measure, but they are presented in their original form. By combining social research with multi-criteria methodologies, transparency of the decision-making process is increased. In this way, the policy-maker is able to make sound decision and is hold responsible for his/her choices.
Keywords: 330